Pemanfaatan Big Data untuk Meningkatkan Perencanaan Strategis di Pemerintahan Daerah Kota Cirebon : Pendekatan Studi Eksploratif - Mohammad Rezza Fahlevvi (Post Graduate School of Government Science, 2025)
This study aims to analyze the adoption level of big data technology in local governments and its contribution to strategic decision-making. Using a descriptive-exploratory approach with mixed methods, data were collected through surveys involving relevant work units and local respondents, totaling 15 respondents, in Cirebon City's local government using a stratified random sampling technique based on the level of information technology utilization, supplemented by in-depth interviews with 10 key informants. The results revealed an increase in significant data adoption from 20% in 2018 to 65% in 2022, positively impacting decision-making efficiency and accuracy. However, limited technological literacy and digital infrastructure remain significant challenges. The novelty of this study lies in its focus on integrating local dimensions into significant data adoption, particularly within Cirebon City’s regional government, an area rarely explored in the existing literature. This study also provides a unique contribution by identifying specific challenges in developing countries, such as infrastructure gaps and organizational cultural barriers, and offering context-specific recommendations. Practically, this study recommends enhancing technological capacity, fostering collaboration with academic institutions, and developing regulations to ensure ethical and transparent data use. The study opens opportunities for further research on cross-country analysis and the long-term impacts of significant data adoption.